Origins of Context-Dependent Gene Repression by Capicua - Forés, Marta (PLoS Genet, 2015)
Receptor Tyrosine Kinase (RTK) signaling pathways induce multiple biological responses, often by regulating the expression of downstream genes. The HMG-box protein Capicua (Cic) is a transcriptional repressor that is downregulated in response to RTK signaling, thereby enabling RTK-dependent induction of Cic targets. In both Drosophila and mammals, Cic is expressed as two isoforms, long (Cic-L) and short (Cic-S), whose functional significance and mechanism of action are not well understood. Here we show that Drosophila Cic relies on the Groucho (Gro) corepressor during its function in the early embryo, but not during other stages of development. This Gro-dependent mechanism requires a short peptide motif, unique to Cic-S and designated N2, which is distinct from other previously defined Gro-interacting motifs and functions as an autonomous, transferable repressor element. Unexpectedly, our data indicate that the N2 motif is an evolutionary innovation that originated within dipteran insects, as the Cic-S isoform evolved from an ancestral Cic-L-type form. Accordingly, the Cic-L isoform lacking the N2 motif is completely inactive in early Drosophila embryos, indicating that the N2 motif endowed Cic-S with a novel Gro-dependent activity that is obligatory at this stage. We suggest that Cic-S and Gro coregulatory functions have facilitated the evolution of the complex transcriptional network regulated by Torso RTK signaling in modern fly embryos. Notably, our results also imply that mammalian Cic proteins are unlikely to act via Gro and that their Cic-S isoform must have evolved independently of fly Cic-S. Thus, Cic proteins employ distinct repressor mechanisms that are associated with discrete structural changes in the evolutionary history of this protein family.